The Role of Cross-Cultural Communication in Enhancing Student Collaboration in a Multicultural Academic Environment - Benedikta Dea Arely; Meilina, Restin (Universitas Nusantara PGRI Kediri, 2025)
Research aim: To analyze the experiences and challenges faced by Management Program students in cross-cultural collaboration and the efforts to overcome these obstacles within an academic environment. Design/Methode/Approach: This study employs a qualitative method using in-depth interviews with cross-cultural student informants at Nusantara PGRI Kediri University. Research Finding: Cultural diversity presents challenges in communication differences but also offers opportunities for the development of knowledge and soft skills. Theoretical contribution/Originality: This study provides new insights into cross-cultural communication and solutions for addressing the dominance of majority cultures. Practitioner/Policy implication: The findings can be used to create an inclusive academic environment through cross-cultural communication training. Research limitation: The study is limited to the academic context and does not cover cross-cultural interactions outside the classroom